Electrochemical conversion of small organic molecules to value-added chemicals and hydrogen/electricity without CO2 emission: Electrocatalysts, devices and mechanisms - Jianwen Liu; Guodong Fu; Yuanfeng Liao; Wangji Zhang; Xiuan Xi; Fengzhan Si; Lei Wang; Jiujun Zhang; Xian-Zhu Fu; Jing-Li Luo (eScience)
The electrochemical conversion of small organic molecules to value-added chemicals and hydrogen/electricity without CO2 emissions integrates efficient energy conversions (hydrogen energy or electricity) and value-added chemical productions in one reaction system, which is essentially competitive in the carbon-neutral era. However, the activity, stability, and cost-effectiveness of electrocatalysts, as well as the safety, durability, and scalability of devices, are still challenging for their industrial applications. In addition, a lack of knowledge about relevant and detailed mechanisms restricts the further development of electrocatalysts and devices. A timely review of the electrocatalysts, devices, and mechanisms is essential to shed lights on the correct direction towards further development. In this review, the advances in the design of electrocatalysts, fabrication of devices, and understanding of reaction mechanisms are comprehensively summarized and analyzed. The major challenges are also discussed as well as the potential approaches to overcoming them. The insights for further development are provided to offer a sustainable and environmentally friendly approach to cogeneration of energy and chemicals production.